STUDI DAMPAK TUTUPAN LAHAN TERHADAP SIMPANAN KARBON DI KAWASAN HUTAN CEMPAKA, KECAMATAN PRIGEN, PASURUAN, JAWA TIMUR - Azurianti Azurianti; Iva Dewi Lestariningsih; Sugeng Prijono; Akmaludin Dimas Anggara; Sarifudin Lathif (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Human activities and global warming cause forest fires that impact increasing carbon emissions, destroy forest biodiversity and destroy soil properties. This research is needed to examine carbon storage and soil physical properties on various types of land cover in the Cempaka Forest area, which will later be used as a basis for carrying out restoration and conservation actions. This study used four observation points: Timber Forest Products, Non-Timber Forest Products, Pine, and Shrubs land cover. Carbon storage was measured in the Cempaka forest using the standard RaCSA procedure. The results showed that land cover differences significantly affect the value of carbon storage, with the highest value for storing carbon being the land cover of HHK. However, the difference in land cover did not cause different results on the physical properties of the soil. Correlation and simple regression between the value of carbon storage and other parameters show that carbon storage is strongly influenced by tree biomass and litter, with respective values ​​of 94% and 21%.